The effect of age and carbohydrate and protein sources on digestibility, fecal microbiota, fermentation products, fecal IgA, and immunological blood parameters in dogs - Maria, A. P.J. [UNESP]; Ayane, L. [UNESP]; Putarov, T. C. [UNESP]; Loureiro, B. A. [UNESP]; Neto, B. P.; Casagrande, M. F. [UNESP]; Gomes, M. O.S.; Glória, M. B.A.; Carciofi, A. C. [UNESP] (Oxford University Press (OUP), 2017)
The present study compared the effects of diets formulated with fibers of different fermentability and protein sources of animal or vegetable origins on old and adult dogs. The experiment was organized in a 3 (diets) × 2 (ages) factorial arrangement, totaling 6 treatments. Thirty-six Beagle dogs were used (18 old dogs [10.2 ± 1.0 yr] and 18 young adult dogs [2.6 ± 0.9 yr]), with 6 dogs per treatment. Three diets with similar compositions were used: a nonfermentable insoluble fiber source (sugarcane fiber) and chicken byproduct meal (nonfermentable fiber [NFF] diet), a fermentable fiber source (beet pulp) and chicken byproduct meal (fermentable fiber [FF] diet), and soybean meal as a protein and fiber source (soybean meal [SM] diet). Data were evaluated using the MIXED procedure and considering the effects and interactions of block, animal, diets, and age. Means were compared using Tukey’s test (P < 0.05). Age × diet interactions were evaluated when P < 0.1. Old dogs had a reduced coefficient of total tract apparent digestibility of DM, which was explained by the age and diet interaction of CP and fat digestibility that was lower for old than for adult dogs fed the FF diet (P < 0.05). The SM diet obtained higher DM, OM, CP, and fiber digestibility compared with the NFF diet (P < 0.05). The feces of dogs fed the NFF diet had increased DM content (P < 0.05). The short-chain fatty acids (SCFA) did not change by age group and were higher for dogs fed the FF and SM diets compared with dogs fed the NFF diet (P < 0.05). An age and diet interaction was observed for lactate and was increased in the feces of old dogs compared with adult dogs fed the FF diet (P < 0.05). Fecal putres-cine, cadaverine, and spermine were increased for old dogs compared with adult dogs (P < 0.05), and the spermidine fecal concentration was increased for dogs fed the SM diet regardless of age (P < 0.05). Old dogs had reduced peripheral T and B lymphocytes (P < 0.05). An age and diet interaction was observed for fecal IgA (P < 0.001). Adult dogs fed the SM diet had increased IgA in feces compared with animals fed the NFF and FF diets (P < 0.05). However, for old dogs, both the FF and SM diets induced increased IgA compared with the NFF diet (P < 0.05). In conclusion, beet pulp may reduce digestibility and induce increased lactate in the feces of old dogs. The protein and oligosaccharides of soybean meal are digestible by dogs, induce the production of SCFA and spermidine, and increase fecal IgA. Old dogs had increased putrecine, cadaverine, and spermine fecal concentrations.
Keywords: Biogenic amines; Old dogs; Short-chain fatty acids; Soybean meal